Temporal and Spatial Uncertainty of Erosion Soil Loss from an Argisol Under Sugarcane Management Scenarios - Mendonça,Patrícia Gabarra (2018)
ABSTRACT The identification of erosion-susceptible areas is fundamental for the adoption of soil conservation practices. Thus, the best way to estimate the spatial pattern of soil erosion must be identified, in which the process uncertainties are also taken into consideration. The purpose of this study was to evaluate the spatial and temporal uncertainty of soil loss under two scenarios of sugarcane harvest management: green cane (GC) and burnt cane (BC). The study was carried out on a 200-ha area, in Tabapuã, São Paulo State, Brazil. A regular 626-point sampling grid was established in the area, with equidistant intervals of 50 m and a final plant density of about 3.3 samples per ha. The probability that the soil loss would exceed the tolerable limit of 6.67 t ha-1 yr-1 was estimated for each management scenario and after the five harvests. The temporal uncertainty was determined by integrating the estimated annual probabilities, representing the harvests. Areas with soil loss risks above the threshold were identified based on probability maps, generated from the individual and combined dichotomous variables. Soil losses from the BC were highest, during all five harvests. With the exception of the 5th harvest and the entire cultivation cycle under GC, all soil loss estimates were spatially dependent. From the 4th harvest under GC, the probability of the soil loss exceeding the threshold was above 80 % in zero percent of the area, whereas, for BC, the probability exceeded 80 % in 40 % of the area. The production cycle allowed the delimitation of priority areas for the adoption of conservation practices in each management. In the BC, areas with steeper slopes were more likely to exceed the threshold with lower uncertainties.